EFFICIENT ALGORITHMS FOR THE REVERSE SHORTEST PATH PROBLEM ON TREES UNDER THE HAMMING DISTANCE - TAYYEBI, Javad; AMAN, Massoud (Yugoslav Journal of Operations Research; Vol 27 No 1 (2017), 2016)
Given a network G(V;A; c) and a collection of origin-destination pairs with prescribed values, the reverse shortest path problem is to modify the arc length vector c as little as possible under some bound constraints such that the shortest distance between each origin-destination pair is upper bounded by the corresponding prescribed value. It is known that the reverse shortest path problem is NP-hard even on trees when the arc length modifications are measured by the weighted sum-type Hamming distance. In this paper, we consider two special cases of this problem which are polynomially solvable. The first is the case with uniform lengths. It is shown that this case transforms to a minimum cost flow problem on an auxiliary network. An ecient algorithm is also proposed for solving this case under the unit sum-type Hamming distance. The second case considered is the problem without bound constraints. It is shown that this case is reduced to a minimum cut problem on a tree-like network. Therefore, both cases studied can be solved in strongly polynomial time.